Exercise Preconditioning Promotes Autophagy to Cooperate for Cardioprotection by Increasing LC3 Lipidation-Associated Proteins - Wan, Dong-Feng; Pan, Shan-Shan; Tong, Yi-Shan; Huang, Yue (Frontiers in Physiology, 2021)
The cardioprotection of exercise preconditioning (EP) has been well documented. EP can be divided into two phases, that is the induction of exercise preconditioning (IEP) and the protection of exercise preconditioning (PEP). PEP is characterized by biphasic protection, including early exercise preconditioning (EEP) and late exercise preconditioning (LEP). LC3 lipidation-mediated autophagy plays a pivotal role in cardioprotection. This study aimed to investigate the alterations of LC3 lipidation-associated proteins during EP-induced cardioprotection against myocardial injury induced by exhaustive exercise (EE) was used in a rat model of EP. These rats were subjected to an intermittent exercise consisting of four periods, with each period including 10 min of running at 30 m/min and 0% grade (approximately 75%VO2max) followed by 10 min of intermittent rest. A model of EE-induced myocardial injury was developed by subjecting rats to a consecutive running (30 m/min, 0% grade) till exhaustion. Following EEP, the colocalization of LC3 with Atg7 was significantly increased, and LC3-I, LC3-II, LC3-II/LC3-I, Atg7, Atg4B and Atg3 levels were significantly increased. Atg7, Atg4B and Atg3 mRNAs were all significantly up-regulated, and LC3 mRNAs tended to be higher. Following LEP, Atg4B and Atg3 levels were significantly increased. Atg7, Atg4B and Atg3 mRNAs were all significantly up-regulated, and LC3 mRNAs tended to be higher. A group of rats was subjected to EEP followed by EE, and the co-localization of LC3 with Atg7 was significantly increased, while LC3-I, LC3-II, LC3-II/LC3-I, Atg7, Atg4B and Atg3 levels were also significantly increased. Moreover, there was a significant increase in the co-localization of LC3 with Atg7, LC3-I, LC3-II, Atg7 and Atg4B levels during LEP followed by EE. The formation of autophagosome during LEP followed by EE may have been weaker than that during EEP followed by EE due to the lower lipidation of LC3. EP may promote autophagy to maintain cell homeostasis and survival, which cooperates for cardioprotection of alleviating exhaustive exercise-induced myocardial injury by increasing LC3 lipidation-associated proteins.